Morfološke značilnosti, razširjenost in opis habitata vrste Dolichus halensis v Sloveniji (Coleoptera: Carabidae): krešiči v agrarnih sistemih - Kapla, Andrej (Acta entomologica slovenica (Ljubljana), 2007)
The carabid Dolichus halensis (Schaller, 1783) is a rare species in Slovenia, but can be locally very abundant. It appears in two colour morphs, among which the brighter morph with red-brown spot is more abundant, the dark morph presents only 22% in the population. Colour morphs in this species are independent of generation and sex. This is a species of agricultural landscape, which can be negatively effected by unsuitable field management. In the paper some possibilities of the use of predatory beetles, such as Dolichus halensis, in the pest biocontrol in the term of sustainable use of large field complexes in Slovenia are considered.
Keywords: entomologija; favna; hrošči; Slovenia; Slovenija